2015
DOI: 10.1002/jez.1914
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the myostatin gene in the adductor muscle of the Pacific lion‐paw scallop Nodipecten subnodosus in association with growth and environmental conditions

Abstract: The cDNA sequence of the myostatin gene in the Pacific lion-paw Nodipecten subnodosus (Ns-mstn) was characterized, and the temporal expression during grow-out was analyzed for the first time in a scallop. Ns-mstn encodes a 459-amino-acid protein in which two propeptide proteolytic sites were identified, the previously recognized (RSKR) and a second one at position 266-269 aa (RRKR). The alternative furin cleavage site could be related with post-translational processing, or it could be a tissue-specific mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 96 publications
(120 reference statements)
2
11
0
Order By: Relevance
“…Tissue-specific expression profile indicated that MSTN mRNA levels were found to be highest in adductor muscle, which was in keeping with the result of C. farreri, A. purpuratus, A. irradians, N. subnodosus and mammalian MSTN (Hu et al 2010;Guo et al 2012;Morales-Collio et al 2014;Morelos et al 2015). It was suggested that a highly conservation of role in muscle development.…”
Section: Discussionsupporting
confidence: 76%
“…Tissue-specific expression profile indicated that MSTN mRNA levels were found to be highest in adductor muscle, which was in keeping with the result of C. farreri, A. purpuratus, A. irradians, N. subnodosus and mammalian MSTN (Hu et al 2010;Guo et al 2012;Morales-Collio et al 2014;Morelos et al 2015). It was suggested that a highly conservation of role in muscle development.…”
Section: Discussionsupporting
confidence: 76%
“…For transcriptomic analysis, two pools (~100 mg each) were used per treatment ( Fig 1A). The RNA extraction was assessed following the methodology previously described for the scallop Nodipecten subnodosus RNA extraction [35], using the TriPure reagent (Roche Diagnostics, Indianapolis, IN, USA), followed by ethanol/chloroform purification and DNAse cleaning. Samples were determined for RNA concentration using a NanoDrop 2000/ 2000c1 spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA), and electrophoresis was performed to evaluate RNA quality.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…Good quality RNA from a total of 20 Pools (two per treatment per tissue) were sent to the Laboratorio Nacional de Genómica para la Biodiversidad (LANGEBIO, Laboratory of Genomics Services, CINVESTAV, Campus Irapuato, GTO, MX) to create and sequence the RNA-seq libraries using the Illumina Next-Seq1 (San Diego, CA, USA). For RT-qPCR analysis, the cDNA synthesis was performed following the methodology previously reported to quantify gene relative expression levels in N. subnodosus [35].…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…At the begining of frlowering, a sample was taken to perform the expression analysis of the 9-cis-epoxycarotenoid gene (PvNCDE1) [54]. Total RNA isolation, cDNA synthesis and real-time PCR amplification were performed following the methodology reported by Morelos et al [55], and the relative expression of PvNCDE1 was estimated following the model proposed by Hellemans et al [56]. One-way ANOVA followed by Tukey's exact test was performed using STATISTICA 8.0 (StatSoft, Inc.).…”
Section: Salinity Stress By Nacl In the Bean Crop (Phaseolus Vulgarismentioning
confidence: 99%